2016
DOI: 10.18331/brj2016.3.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Fungal protein and ethanol from lignocelluloses using Rhizopus pellets under simultaneous saccharification, filtration and fermentation (SSFF)

Abstract: Please cite this article as: FazeliNejad S., Ferreira J.A., Brandberg T., Lennartsson P.R., Taherzadeh M.J. Fungal protein and ethanol from lignocelluloses using Rhizopus pellets under simultaneous saccharification, filtration and fermentation (SSFF). Biofuel Research Journal 9 (2016) SSFF can be used for production of ethanol and biomass from wheat straw.Glucose present in the feed controlled the assimilation of xylose and acetic acid.The fungal growth rate was found not to be influenced by the feed comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…Most ethanol production occurred during the first 24 h, followed by its utilization by filamentous fungi as cultivant. Similar phenomena have been reported by FazeliNejad et al [43] for Rizhopus sp., utilizing ethanol as a carbon source after 48 h cultivation. From an industrial biorefinery viewpoint, ethanol produced through fungal cultivation in vinasse has the potential to be reintroduced into the molasses fermentation broth processed downstream, which has already been established to increase process efficiency.…”
Section: The Organic Removal and Metabolite Production Of Fungi In VIsupporting
confidence: 91%
“…Most ethanol production occurred during the first 24 h, followed by its utilization by filamentous fungi as cultivant. Similar phenomena have been reported by FazeliNejad et al [43] for Rizhopus sp., utilizing ethanol as a carbon source after 48 h cultivation. From an industrial biorefinery viewpoint, ethanol produced through fungal cultivation in vinasse has the potential to be reintroduced into the molasses fermentation broth processed downstream, which has already been established to increase process efficiency.…”
Section: The Organic Removal and Metabolite Production Of Fungi In VIsupporting
confidence: 91%
“…The current 15.7% increase in the CP content of the fermented substrate may be due to the high production of fungal cell mass, which led to a reduction of reducing sugars, and consequently the production of protein within the fungus population. This is in agreement with other previous studies [42][43][44] that demonstrated that some fungal species were able to increase the CP level in agro-industries wastes.…”
Section: Discussionsupporting
confidence: 94%
“…Similar observations on the production of fungal biomass and ethanol using acid-pretreated wheat straw slurry were obtained in a previous study while using zygomycetes strains of filamentous fungus, Rhizopus sp. ; however the biomass yields obtained was only up to 0.34 g biomass/g consumed monomeric sugars and acetic acid [ 28 ].…”
Section: Resultsmentioning
confidence: 99%